(untitled) (Research, Society and Development, 2021)
The Supervised Curriculum Internship (SCI) is a compulsory curricular component, in which pre-professional practice activities are carried out, characterizing itself as an important stage in the formation of the future teacher. In the school environment, where the SCI is developed, the figure of the supervising teacher (ST) emerges, responsible for leading the intern on this formative journey. In this sense, this research aimed to describe the perceptions and assessments from a ST of the SCI, about their supervision of interns. It was a research with a qualitative approach, descriptive in nature, using the case study technique. The semi-structured interview was used as an instrument. Participated in the study a teacher of basic education, acting as supervisor of SCI. For data analysis, the Content Analysis Technique was used. In function of the results, the teacher perceives her performance as ST from three categories: reception in the school environment, aspects of teacher professionalism and reflections on the role of ST. It is concluded that the selection of the ST is of utmost importance and that it must be carried out through agreements between the university and the school. It is possible to affirm that it is necessary for the ST to really know its role and the importance of its performance in teacher education. Furthermore, the university needs to have a horizontal and committed relationship with the school, understanding that it needs it to carry out the SCI effectively.